Capacity of the legal framework of public health institutions in Mexico to support their functional integration - Ignacio Ibarra; Gabriel Martínez; Nelly Aguilera; Emanuel Orozco; Germán E Fajardo-Dolci; Miguel A González-Block (Instituto Nacional de Salud Pública, 2013)
Objective. Evaluate the capacity of the federal legal framework to govern financing of health institutions in the public sector through innovative schemes -otherwise known as functional integration-, enabling them to purchase and sell health services to and from other public providers as a strategy to improve their performance. Materials and methods. Based on indicators of normative alignment with respect to functional integration across public health provider and governance institutions, content analysis was undertaken of national health programs and relevant laws and guidelines for financial coordination. Results. Significant progress was identified in the implementation of agreements for the coordination of public institutions. While the legal framework provides for a National Health System and a health sector, gaps and contradictions limit their scope. The General Register of Health is also moving forward, yet it lacks the necessary legal foundation to become a comprehensive tool for integration. The medical service exchange agreements are also moving forward based on tariffs and shared guidelines. However, there is a lack of incentives to promote the expansion of these agreements. Conclusions. It is recommended to update the legal framework for the coordination of the National Health System, ensuring a more harmonious and general focus to provide functional integration with the needed impulse.